Effect Of Rabal Probiotic Dosage Application In Fish Feed On Growth And Survival Of Gouramy (Osphronemus gouramy) - Violentina Violentina; Firman Firman; Suharun Martudi (University of Prof. Dr. Hazairin, SH, 2022)
Gouramy (Osphronemus gouramy) growth relatively slowly, so efforts are needed to make these fish grow fast, among others through the application of the probiotic Rabal. This study aims to obtain the optimal dose of Rabal probiotics in feed on the growth and survival of gouramy size 4-6 cm.. This research was carried out in November 2021-January 2022 for 60 days in Bukit Peninjauan 1 Village, Sukaraja District, Seluma Regency, Bengkulu Province. The study used a completely randomized design (CRD) consisting of 4 treatments and 6 replications. P0 (control) without probiotics; P1 (Probiotics 10 ml/100 grams of feed), P2 (Probiotics 20 ml/100 grams of feed), and P3 (probiotics 30 ml/100 grams of feed).The results of the analysis of variance and orthogonal polynomials showed that the application dose of Rabal probiotics in feed had a significant effect on absolute weight gain and specific growth rate. The optimal application dose of 20.07 ml per 100 grams of feed resulted in an absolute increase of 38.98 grams of gouramy (P2) with a specific growth rate of 2.44%.